The Influence of Leadership and Training on Motivation and Its Impact on Employee Performance at Riva Restaurant and Bar - Ekadharma Susila, Bagus Putu; Ariantini, Putu Oka (Akademi Komunitas MAPINDO, 2024)
This research aims to analyze the influence of leadership and training on motivation and its impact on employee performance at Riva Restaurant and Bar, Kuta - Bali. The respondents for this research were all 44 employees. The sample uses saturated sampling. Data collection methods use interviews, questionnaires and documentation. The analysis technique in research uses path analysis techniques (Path Analysis). Respondents' answers will be processed using a Likert scale. Further analysis was carried out using Path Analysis assisted by the SPSS 20 for Windows software program. The results of research on path analysis test 1 show that leadership and training have a positive and significant effect on employee motivation. The magnitude of the influence of leadership and training on motivation is 41.2% and 31.5%. And the results of research on path analysis test 2 show that leadership, training and motivation have a positive effect on employee performance. The magnitude of the influence of leadership, training and motivation on employee performance is 28.7%, 29.8% and 32.9%. Motivation as an intermediate variable has a positive influence and is able to mediate the relationship between leadership and training on employee performance. Keywords: Leadership, Training, Motivation, Employee Performance.